2019
DOI: 10.1093/ckj/sfz082
|View full text |Cite
|
Sign up to set email alerts
|

Small steps towards the potential of ‘preventive’ treatment of early phosphate loading in chronic kidney disease patients

Abstract: Few clinical studies have investigated the value of phosphate (P)-lowering therapies in early chronic kidney disease (CKD) patients in whom hyperphosphataemia has not yet clearly developed and they report conflicting and even unexpected results. In this issue of Clinical Kidney Journal, de Krijger et al. found that sevelamer carbonate (4.8 g/day for 8 weeks) did not induce a significant reduction of pulse wave velocity (PWV) and that fibroblast growth factor 23 (FGF23) did not decrease despite a decline in 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These findings challenged to some extent the concept that "preventive" P binder therapy is a useful approach, at least over this short period. Interestingly, in a subgroup of patients with absent or limited abdominal VC, treatment did result in a statistically significant reduction in adjusted PWV, suggesting that PWV is amenable to improvement in this subset (120,122). On the other hand, Toussaint et al (121) recently reported that lanthanum carbonate did not affect arterial stiffness or VC in CKD G3b-4 patients; however, an absence of a significant decline in 24-h urine P excretion seems difficult to explain.…”
Section: Phosphate Bindersmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings challenged to some extent the concept that "preventive" P binder therapy is a useful approach, at least over this short period. Interestingly, in a subgroup of patients with absent or limited abdominal VC, treatment did result in a statistically significant reduction in adjusted PWV, suggesting that PWV is amenable to improvement in this subset (120,122). On the other hand, Toussaint et al (121) recently reported that lanthanum carbonate did not affect arterial stiffness or VC in CKD G3b-4 patients; however, an absence of a significant decline in 24-h urine P excretion seems difficult to explain.…”
Section: Phosphate Bindersmentioning
confidence: 96%
“…On the other hand, Toussaint et al ( 121 ) recently reported that lanthanum carbonate did not affect arterial stiffness or VC in CKD G3b-4 patients; however, an absence of a significant decline in 24-h urine P excretion seems difficult to explain. Therefore, interpretation of the scarce and heterogeneous observations described in early CKD remains difficult, and the possibility of beneficial effects of a “preventive” treatment may not yet be completely disregarded ( 122 ). Finally, significant beneficial effects of a fixed dose of ferric citrate in advanced ND-CKD patients merit further study ( 123 ), since it was not a placebo-controlled randomized clinical trial (RCT), about 1/3 of patients in the “standard of care” arm took Ca-based P binders, and the outcome was a composite end-point.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Phosphate binders are the mainstay of pharmacological therapy for hyperphosphatemia in CKD patients [ 13 , 25 ]. They are usually prescribed at advanced CKD stages when hyperphosphatemia is evident, but there is an ongoing reexamination of the potential benefits of ‘preventive’ treatment of early phosphate overload in CKD patients [ 26 , 27 ]. Well designed, larger, long-term clinical trials are needed to respond this critical question.…”
Section: Phosphate and Ckdmentioning
confidence: 99%
“…Thus, dialysis clearance is frequently not sufficient to efficiently clear phosphate, and phosphate levels may increase years before the need for dialysis in the natural history of kidney disease. Thus, oral phosphate binders that prevent gut dietary phosphate absorption are key tools to prevent phosphate toxicity [9]. Potassium binders are also routinely used [10].…”
mentioning
confidence: 99%